Particle tracers and image analysis for surface flow observations. (17th September 2015) - Tauro, Flavia
Abstract : Traditional observational methodologies have proved insufficient to thoroughly characterize the hydrological response of natural environments. In this context, recent efforts have fostered unprecedented observational methodologies for hydrological processes at the interface of multiple engineering and scientific fields and water science. This overview outlines latest advancements in the observation of surface flows through a novel methodology based on the combined use of high‐visibility tracer particles and digital image acquisition and processing. This low‐cost measurement system has been designed and tested in laboratory settings and natural environments, such as rill flow in natural hillslopes and riverine ecosystems. Comparison of this novel flow sensing method to traditional tracing systems has suggested that the use of multidisciplinary and unintended technology can greatly contribute to advance standard practice in environmental monitoring and to open novel research avenues in water science. WIREs Water 2016, 3:25–39. doi: 10.1002/wat2.1116 This article is categorized under: Science of Water > Methods